The Effects of a Cognitive Dual Task on Jump-landing Movement Quality - Schnittjer, Amber; Simon, Janet E.; Yom, Jae; Grooms, Dustin R. (International Journal of Sports Medicine, 2020)
Investigations on movement quality deficits associated with jump landing are numerous, however, these studies are often performed in laboratories with little distraction to the participant. This is contrary to how injury typically occurs secondary to sport-specific distraction where the athlete is cognitively loaded during motor performance. Thus, the purpose of this study was to determine the effect of a cognitive load on jump-landing movement quality. A dual-task design was used to determine the effects of a dual-task on tuck jump movement quality in 20 participants. There were three cognitive conditions (no cognitive task, easy-cognitive task, and difficult-cognitive task). The dual task elicited statistically significant changes in overall tuck jump score (movement quality) across the conditions with tuck jump score increasing from 3.52±1.64 baseline to 4.37±1.25 with the easy-cognitive task to 4.67±1.24 with the difficult-cognitive task. The findings of this study may be useful to screen for individuals at risk of lower extremity injury utilizing the tuck jump when paired with a cognitive task. The screening would then identify individuals who may have poor neuromuscular control when cognitively loaded.
Keywords: tuck jump; real-time assessment; neuromuscular